Role of domain interactions during the amyloid formation of yeast phosphoglycerate kinase - Agócs, Gergely (Acta Biologica Szegediensis, 2006)
Beta-amyloids are known to be the cause of an increased oxidative stress, which manifests in a higher rate of membrane lipid oxidation in some diseases. There are several proteins that are built up of two structural domains and are deposited full-length in amyloid plaques formed during different diseases. Several publications prove the role of the domain-domain interactions in protein folding, but the effect of the domain interactions on misfolding and amyloid formation has not been tested yet. In this work we show the importance of the inter-domain interactions in amyloid formation. A model protein system based on mutants of the two-domain protein yeast phosphoglycerate kinase was used to study the role of domain interactions in the amyloid formation of multi-domain proteins. After the initiation of the amyloid formation, tryptophan fluorescence spectroscopy was used to detect the structural changes of the two domains from 5 minutes to 4 days. We compared the kinetics of amyloid formation of the individual domains with that of the intact protein. For all mutants, electron micrographs proved the formation of amyloid fibrils after 5 days. We found that the aggregation-coupled conformation changes of the two domains are synchronized in the protein through the domain-domain interactions.